Research progress and application strategies of sugar transport mechanisms in rice - Li, Jun; He, Changcai; Liu, Shihang; Guo, Yuting; Zhang, Yuxiu; Zhang, Lanjing; Zhou, Xu; Xu, Dongyu; Luo, Xu; Liu, Hongying; Yang, Xiaorong; Wang, Yang; et al. (Frontiers in Plant Science, 2024)
In plants, carbohydrates are central products of photosynthesis. Rice is a staple that contributes to the daily calorie intake for over half of the world's population. Hence, the primary objective of rice cultivation is to maximize carbohydrate production. The "source-sink" theory is proposed as a valuable principle for guiding crop breeding. However, the "flow" research lag, especially in sugar transport, has hindered high-yield rice breeding progress. This review concentrates on the genetic and molecular foundations of sugar transport and its regulation, enhancing the fundamental understanding of sugar transport processes in plants. We illustrate that the apoplastic pathway is predominant over the symplastic pathway during phloem loading in rice. Sugar transport proteins, such as SUTs and SWEETs, are essential carriers for sugar transportation in the apoplastic pathway. Additionally, we have summarized a regulatory pathway for sugar transport genes in rice, highlighting the roles of transcription factors (OsDOF11, OsNF-YB1, OsNF-YC12, OsbZIP72, Nhd1), OsRRM (RNA Recognition Motif containing protein), and GFD1 (Grain Filling Duration 1). Recognizing that the research shortfall in this area stems from a lack of advanced research methods, we discuss cutting-edge analytical techniques such as Mass Spectrometry Imaging and single-cell RNA sequencing, which could provide profound insights into the dynamics of sugar distribution and the associated regulatory mechanisms. In summary, this comprehensive review serves as a valuable guide, directing researchers toward a deep understanding and future study of the intricate mechanisms governing sugar transport.